3D Printing in Dentistry and Targeted Drug Delivery: A New Era of Personalized and Precision Medicine (Asian Journal of Pharmaceutics (AJP), 2026)
Three-dimensional (3D) printing, a transformative additive manufacturing technology, has ushered in a new era of personalized and precision medicine in both dentistry and drug delivery. This review explores the evolution and integration of 3D printing with digital workflows such as computer-aided design and computer-aided manufacturing, highlighting its application in fabricating custom dental prostheses, orthodontic aligners, surgical guides, and implant planning tools. It also examines the development of patient-specific drug delivery systems using 3D-printed devices with programmable release profiles, tailored for pediatric, geriatric, and chronic disease management. Core printing technologies such as stereolithography, digital light processing, selective laser sintering, fused deposition modeling, and photopolymer jetting are compared based on precision, material compatibility, and clinical use. The review further delves into recent advancements in regenerative dentistry, such as bioactive scaffolds and stem-cell-loaded constructs for tissue engineering. Challenges like biomaterial cytotoxicity, postprocessing inaccuracies, regulatory gaps, and cost barriers are analyzed alongside emerging solutions. Future directions, including four-dimensional materials, artificial intelligence-driven predictive modeling, point-of-care manufacturing, and sustainable printing materials, are proposed. This synthesis bridges engineering and clinical practice, underlining the profound potential of 3D printing to transform oral healthcare and drug therapy delivery